2007
DOI: 10.1145/1242060.1242062
|View full text |Cite
|
Sign up to set email alerts
|

The multilevel hypernetwork dynamics of complex systems of robot soccer agents

Abstract: A mathematical formalism is sketched for representing relational structure between agents. n-ary relations, n > 2, require hypernetworks, which generalize binary relation networks. n-ary relations on sets create structure at higher levels of representation to the elements in multilevel systems. The state of a system is represented by its multilevel relational structure. The dynamics of a system are represented by state changes through time. These can be continuous with no change in the hypernetwork topology, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…In the present study, we have extended the approach by Johnson and Iravani ( 2007 ) by introducing compound variables, e.g., local dominance, which capture the structure and dynamics of cooperative and competitive interactions in the following ways:…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have extended the approach by Johnson and Iravani ( 2007 ) by introducing compound variables, e.g., local dominance, which capture the structure and dynamics of cooperative and competitive interactions in the following ways:…”
Section: Introductionmentioning
confidence: 99%
“…Gould and Gatrell [3] suggested that Atkin's method could be applied to soccer analysing the 1977 Football Association Cup Final in the UK. Johnson [4] suggested applying the method to robot soccer [5] and it was further developed by Johnson and Iravani [5] using Johnson's theory of hypernetworks [6]. Recently Ramos et al [7] showed how the hypernetwork approach can be applied in sports science.…”
Section: Multidimensional Structure In Robot Soccermentioning
confidence: 99%
“…According to hypergraph theory, nodes in common set from layer N can be assembled as a new node at Layer N+1 [12] , as illustrated in Figure 2. In cyberspace cyber missions are composed of concurrent or cooperative services and services exert their function depend on assets.…”
Section: Composition Of Cyberspace Hypergraphmentioning
confidence: 99%
“…Hypergraph is a generalization of graph theory proposed by Berge [10] designed to represent a set of subsets on a finite set. It has been applied for domains where multilevel structure relations with dynamics such as co-authorship exist [11] and robot-robot interactions [12] . We propose to employ hypergraph to exploit the multi-layer relations among homogeneous entities and heterogeneous entities in cyberspace.…”
Section: Introductionmentioning
confidence: 99%